Chemo‐ and Regioselective Reduction of 5, 15‐Diazaporphyrins Providing Antiaromatic Azaporphyrinoids. Issue 12 (3rd February 2016) - Yamaji, Ayaka; Tsurugi, Hayato; Miyake, Yoshihiro; Mashima, Kazushi; Shinokubo, Hiroshi
Abstract: Reagent‐controlled chemo‐ and regioselective reduction of 5, 15‐diazaporphyrins has been developed. The selective reduction of carbon–carbon double bonds of diazaporphyrins provides 18 π aromatic isobacteriochlorin‐type products, whereas the reduction of carbon–nitrogen double bonds leads to selective formation of 20 π N, N ′‐dihydrodiazaporphyrins in excellent yields. The distinct antiaromatic character of N, N ′‐dihydrodiazaporphyrins has been revealed. The free‐base N, N ′‐dihydrodiazaporphyrin exhibits slower inner NH tautomerism than that in the corresponding 18 π porphyrins. Abstract : Reagent‐controlled chemo‐ and regioselective reduction of 5, 15‐diazaporphyrins has been developed. The selective reduction of carbon–carbon double bonds of diazaporphyrins provides aromatic isobacteriochlorin‐type products, whereas the reduction of carbon–nitrogen double bonds leads to N, N ′‐dihydrodiazaporphyrins with distinct antiaromatic character.